ECONOMIC SECURITY OF SMALL BUSINESS IN RUSSIA - YURY ALEKSEEVICH Burtsev (Мир новой экономики)
The article deals with the problems that small business in Russia face today and uncovers the basic barriers for small businesses, as well as their development trends, in times of crisis.The article argues that small business promotes an increase in the tax base for the budgets of different levels, helping to reduce unemployment and provide the market complete of goods and services. Small business affects the development of the economy, stabilizes its internal processes, and has a stimulating effect.The author speculates that nowadays small business in Russia is experiencing serious difficulties that consistent work is needed to overcome, above all, it is necessary to further improve the legislation, financial support for small businesses, to improve the efficiency of regional development programs for small andmedium-sized businesses, to regulate economy, to eliminate administrative barriers and overcome corruption. Also, the article notes that small business in Russia is characterized by the duality of its position. On the onehand, small business is provided with many benefits, subsidies and aid. On the other hand, it becomes the firsttarget in case of even the minimal crisis.